Psychotropic Drug Use in Children with Autism Spectrum Disorder Admitted to a Training and Research Hospital Outpatient Clinic: A Retrospective Cross-Sectional Study - Uygun, Sabide Duygu; Çakmak, Fatma Hülya; Canlı, Merve; Temeltürk, Rahime Duygu; Efe, Ayşegül; Gürel, Yusuf; Açıkel, Sadettin Burak; Çetinkaya, Miray (Journal of Child Science, 2020)
This study aimed to examine demographic and clinical variables, psychiatric comorbidities, the prevalence of psychotropic drug use, relationships between drug use, demographic and clinical variables, and predictors of drug use in children with autism spectrum disorder (ASD) admitted to a training and research hospital outpatient clinic. Four hundred and eleven children with ASD admitted to the Department of Child and Adolescent Psychiatry, Dr. Sami Ulus Maternity and Children's Health and Diseases Training and Research Hospital, between October 1, 2019 and December 31, 2019, were retrospectively reviewed. Demographic and clinical variables, psychiatric comorbidities, and characteristics of drug use for the cases were recorded. Psychotropic drug use was found in 34.3% (n = 141) of the cases. Our results revealed male sex and psychiatric comorbidity as predictors of psychotropic drug use. Antipsychotics were the most prescribed drugs, and the most common psychiatric comorbidity was conduct disorder. Also, children with ASD who had been toilet-trained, and could express sentences but were illiterate, were using psychotropic drugs more often than others. Future multicentered, large clinic-based studies from training and research hospitals should focus on trends of treatment in psychiatric comorbidities accompanying ASD, and constitute a systematic approach for the psychopharmacological treatment of these cases.
Keywords: autism; pharmacotherapy; comorbidity; child psychiatry